The Role of Coenzyme Q10 Supplementation as a Potential Adjunct in the Treatment of Autoimmune Diseases - Bukała, Martyna; Ochyra, Karolina; Pudło, Kornelia; Frydrych, Jowita; Prucnal, Gabriela; Ryba, Karolina; Znamirowska, Katarzyna; Zacher, Klaudia; Walkiewicz, Patrycja; Rakoczy, Anna (Quality in Sport, 2025)
Autoimmune diseases are a heterogeneous group of afflictions whose etiopathogenesis is still incompletely understood. There is a great need to search for new treatment methods because of the difficulty of treatment, the numerous side effects of pharmacotherapy and the life-threatening complications associated with these diseases. The discovered role of mitochondrial dysfunction in the pathogenesis of these conditions and the associated oxidative stress, but also the contribution of coenzyme Q10 to normal mitochondrial function, provided the impetus for research into the use of coenzyme Q10 supplementation as an adjunctive therapy for autoimmune diseases. This review article summarises the role of coenzyme Q10 supplementation in the regulation of impaired processes involved in the pathogenesis of autoimmune diseases and focuses on the potential benefits of coenzyme Q10 supplementation for patients with autoimmune diseases.